Educating Preschoolers to Pro-Environmental Actions: A Metacognition-Based Approach - Martina Rulli; Elsa Bruni; Alberto Di Domenico; Nicola Mammarella (Journal of Education in Science, Environment and Health)
Metacognition is the process of thinking about one's own thinking, learning, and problem-solving strategies. It involves being aware of one's own cognitive processes and knowing how to regulate and monitor them. Sustainability, instead, refers to the ability to maintain or preserve resources and ecosystems for future generations. Here, we draw from the classical metacognitive approach and propose that metacognition plays an important role in sustainability. The PRISMA (Preferred Reporting Items for Systematic Reviews and MetaAnalyses) Statement was used to perform and recode this review. Given that metacognitive abilities develop early during childhood, metacognition can be viewed as a useful approach to teach pro-environmental behavior from early childhood. Although the interaction between metacognition and sustainability in preschoolers appears to be insufficiently explored, the final aim of this review is to offer a new education-based perspective about metacognition that can be implemented in early childhood to foster pro-environmental actions in the long-term.